História dos dogmas, história da teologia, história do pensamento cristão: considerações sobre alguns conceitos da historiografia eclesiástica - Fischer, Joachim (2012)
The article begins based on the premise that Christians, in all times, have wanted to understand their faith intellectually as well (Anselmo de Cantuária, Karl Barth) so as to be able to explain it to other people. The quest for understanding the faith constitutes an essential aspect of the life of the people of God throughout time. The article analyzes different conceptions in approaching this history: such as the history of the dogmas, the history of theology, the history of the Christian doctrine, the history of Christian thought. It especially delves more deeply into the Latin American aspects of this approach (Eduardo Hoornaert, Otto Maduro, Enrique Dussel). Among the conceptualizations, it highlights the concept “history of Christian thought” (Justo L. Gonzalez, Paul Tillich). As the range of the concept is immense, it is necessary to identify the fundamental theological issue of each time period and concentrate on its approach.